Organizing Time for Secular and Religious Purposes: The Contemplacion of Sinners (1499) and the Translation of the Benedictine Rule for Women (1517) of Richard Fox, Bishop of Winchester - Collett, Barry (Studies in church history, 2002)
The career of Bishop Richard Fox was marked by his dedication to hard work and his obsession with the organized management of time. Fox was born about 1448 into a Lincolnshire yeoman family, was educated at local grammar schools and Oxford, was subsequently ordained, and later became a doctoral student at the University of Paris. In 1484 he joined the entourage of the exiled Henry Tudor, who recognized his ability and gave him considerable responsibility in negotiating with the French government and planning the 1485 invasion of England. After Bosworth, Fox became Lord Keeper of the Privy Seal and a member of the royal council with particular responsibility for foreign affairs. He was appointed bishop successively of Exeter, Bath and Wells, Durham, and Winchester. In 1516, he founded Corpus Christi College, Oxford, retired from politics, and returned to Winchester, where he died in 1528.